Plantas medicinais usadas para tratamento de cefaleia: inquérito de herbolários na Feira de Caruaru - Santos, Karllus Andhre Leite de Mendonça; Barros, Francijane de Almeida; Cavalcanti, Adalgisa Maria de Oliveira; Silva, Louana Cassiano da; Martins, Hugo André de Lima; Valença, Marcelo Moraes (Headache Medicine, 2016)
Plants are used for medicinal purposes since the early days of humanity. For a long time it constituted the main form of therapeutic approach, still retaining significant application in developing countries through the popular knowledge. There is an increased demand for plant derived products in developed countries, in the form of supplements or processed extracts to promote health and general well-being. There is still limited to the prescription of herbs for clinical use due to lack of evidence about their effectiveness and possible side effects, despite the consolidated use the popular practice. This study aims to record which are commonly indicated plants and how they are used for the treatment of headache by herbalists in the city of Caruaru.